(untitled) (International Journal of Physiotherapy, 2015)
Background: Back pain is a prevalent and expensive problem in society. 60-80% of people will suffer at least one episode of low back pain sometime in their lives and 30-40% of these will experience low back pain each year. Therefore the need of the following study is to see the effect of proprioceptive neuromuscular facilitation on back muscle strength, pain and QOL in subjects with Chronic Low Back Pain. Methods: Ethical approval was taken before study. Forty patients with chronic low back pain (28 male, 12 female) were included in the study and divided into two groups each containing 20 subjects. All the participants were signed written consent after being informed in detail about the study. Group A has been given the proprioceptive neuromuscular facilitation exercises including Rhythmic Stabilization (RST) and Combination of Isotonics (COI) and Conventional back exercises. Group B was given conventional back exercises only. Outcome measures were taken at the end of one month i.e. after the treatment protocol. VAS, SF-36Questionnaire and Core stability gradation were taken in both groups. Results: There is significant improvement in VAS score in both groups but Group A was having more significant improvement than Group B. Also there is significant improvement in core stability grading and SF 36 score in Group A. Conclusion: It is concluded that proprioceptive neuromuscular facilitation exercises on back is effective in reducing pain and improving core muscle strength in subjects with Chronic Low Back Pain.